Determination of the prevalence and diversity of viral gastroenteritis infections and secretor status in the elderly population of the Tshwane region in South Africa - Mans, Janet (University of Pretoria, 2020)
Dissertation (MSc (Medical Virology))--University of Pretoria, 2019.